Optimization of a Low Power Operational Transconductance Amplifier (OTA) for High Gain in Miniature Devices for Low Frequency Applications (International Journal of Food and Nutritional Sciences, 2019)
Operational Transconductance Amplifiers (OTA) have been optimized for wireless and medical applications, in addition to other low-frequency and low-voltage applications. Even though its supply voltages differ from those employed by operational amplifiers (OPAMPs), they are similar. Since differential input pairs and bias current could potentially be employed to alter an OTA's characteristics, it has been shown advantageous for amplifiers and filters. OTA designs consider several factors, including output swing, power, speed, and gain. We compare the telescopic cascade OTAs via balanced operational OTAs; the former offers low output impedance resulting in inadequate gain. Transistors can be employed in cascades to improve impedance; a common emitter stage is loaded by the emitter of a common base stage. OTAs produce substantial variations in output current from small variations in the input voltage due to their feature of high gain.